A kind of corrosion-resistant and wear-resistant slag welding wire and its preparation method
By combining different flux core materials and controlling the amount of components, especially using the synergistic effects of microcarbon ferrochromium, ferroboron and ferrovana, the problem of insufficient hardness of the welding wire is solved, significantly improving the wear resistance and resistance of the welds Corrosiveness increases the amount of steel over steel of the welded structure.
Patent Information
- Application Number
- CN202411418650.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The hardness of the welds formed by existing welding wires is insufficient, which affects the bearing capacity and service life of the welded structure.
The combination of a variety of different medicament materials is used for combination, and the addition of each component is strictly controlled, especially through the synergistic effects of microcarbon ferrochromium, ferroboron and ferrovana, the number of cracks caused by the thick rod-like structure of the crystal phase is reduced. It also promotes the transformation of the structure to a short rod-shaped structure, and improves the cross-tightness of the crystal phase structure.
It significantly improves the wear resistance and corrosion resistance of the weld, so that the weld has a high hardness. High hardness welds can greatly increase the amount of steel over steel in the welded structure, and the amount of steel over steel in the arc-shaped section shall not be less than 800,000 tons. , the amount of steel over the horizontal section shall not be less than 1.2 million tons.
Smart Images

Figure CN118926769B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of welding materials, and in particular to a corrosion-resistant and wear-resistant slag welding wire and a preparation method thereof. Background Art
[0002] The welding wire plays the role of filling the weld in the welding process, fusing with the base metal to form a weld, ensuring the integrity and load-bearing capacity of the welded structure. The quality of the welding wire directly affects the welding effect. High-quality welding wire can not only improve the surface finish of the welded structure, but also extend the service life of the welded structure. With the continuous development of welding technology, high-quality welding wire is crucial to ensure the long-term stability of the welded structure and improve production efficiency. Therefore, the performance of the welding wire directly affects the reliability and service life of the welded structure. In addition, welding wire is widely used in industrial production, especially in large steel structures, bridges, shipbuilding and other industries, and its performance is particularly important.
[0003] Existing welding wire materials usually use a single alloy or a simple alloy combination, such as low alloy steel and some stainless steel materials. In order to enhance the mechanical properties of the weld in actual application, these materials are widely used in various welding processes. For example, in many industrial workshops, commonly used welding materials include ordinary low alloy high strength steel welding wire, stainless steel welding wire and some other alloyed welding wires, which are used in different welding environments. In addition, in specific welding environments, such as low temperature or corrosive environments, specific composition alloy welding wires are often used to meet the use requirements.
[0004] However, the weld formed by the existing welding wire has insufficient hardness, which will affect the amount of excessive steel in the welded structure during use, thereby reducing the bearing capacity and service life of the welded structure. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a corrosion-resistant and wear-resistant slag welding wire and a preparation method thereof.
[0006] In the first aspect, the present application provides a corrosion-resistant and wear-resistant slag welding wire, the raw materials used include a core flux and a steel strip, and the raw materials used for the core flux include the following components in mass percentage: 35-38% micro-carbon ferrochromium; 8-10% nickel powder; 3-5% ferroboron; 2-4% high-carbon ferromanganese; 2-4% silicon-manganese alloy; 1-5% aluminum powder; 4-8% rutile powder; 1-3% quartz powder; 4-6% fluorite powder; 0.5-2% ferrovanadium; 1-2% ferroniobium; 0.5-1% cobalt powder; 2-2.5% tungsten powder; 1-2% potassium carbonate powder; 2-5% fused magnesia; 1-5% marble powder; 1-2% ferrotitanium; 3-5% flux; and the balance is iron.
[0007] By adopting the above technical scheme, the present application uses a variety of different flux core materials for compounding and strictly controls the addition amount of each component, and obtains a welding wire that can significantly improve the hardness of the weld. Among them, micro-carbon ferrochromium, ferroboron and ferrovanadium play a particularly significant synergistic effect, which can greatly reduce the number of cracks caused by the coarse rod-like structure of the crystal phase inside the weld, and promote the transformation of the coarse rod-like structure to a short rod-like structure, and improve the random distribution, presenting as much staggered random distribution as possible, thereby greatly improving the cross-tightness of the crystal phase structure inside the weld, and also improving the wear resistance and corrosion resistance of the weld, thereby making the weld have a very high hardness, and the high-hardness weld can greatly increase the amount of steel passing through the welding structure. After testing, the arc section of the welding structure using the welding wire of this application has a steel passing amount of not less than 800,000 tons, and the horizontal section has a steel passing amount of not less than 1.2 million tons, which can realize semi-automatic or fully automatic welding of spiral welding and swing welding.
[0008] Preferably, the raw materials used for the drug core further include manganese nitride added in an amount of 4-5wt%.
[0009] Preferably, the added amount of the manganese nitride is 4.6wt%, and the added amount of the tungsten powder is 2.2wt%.
[0010] By adopting the above technical solution, the present application adds a certain amount of manganese nitride to the flux core, wherein the manganese element can provide a certain hardness for the weld, and the nitrogen element can be dissolved into the weld matrix at high temperature to form solid solution strengthening, and form nitrides with some elements in the system, playing a dual role, thereby significantly improving the wear resistance of the weld; at the same time, the nitrogen element can have a good synergistic effect with tungsten powder, forming a high-strength solid solution, causing lattice distortion in the system, thereby further improving the hardness of the weld. At the same time, the present application strictly controls the amount of manganese nitride and tungsten powder added, thereby strictly controlling the weight ratio of the two, and further optimizing the wear resistance and hardness of the weld.
[0011] Preferably, the flux includes one or more of sodium fluorosilicate, potassium feldspar, sodium feldspar and zinc oxide.
[0012] Preferably, the flux comprises sodium fluorosilicate and potassium feldspar in a weight ratio of (1-3):(1-3).
[0013] By adopting the above technical solution, the present application utilizes different fluxes for compounding, which can promote the melting of non-metallic elements in the system, improve the hardness of the weld and the smoothness of the weld surface. Experiments have shown that sodium fluorosilicate and potassium feldspar in a weight ratio of (1-3): (1-3) can maximize the improvement of weld hardness in the system of the present application.
[0014] Preferably, the filling rate of the drug core is 35-42%.
[0015] Preferably, the filling rate of the drug core is 38-40%.
[0016] By adopting the above technical solution, the present application controls the filling rate of the flux core step by step, which not only ensures high compactness and low fluidity during filling, but also ensures smooth and unstuck process during subsequent drawing. If the filling rate is too low, the components of the flux core are prone to flow during drawing and welding, resulting in unstable arc or even arc breaking during welding. At the same time, the inside of the welding wire is loose, and gas will be brought into the molten pool during welding, increasing the number of pores in the weld and greatly reducing corrosion resistance. If the filling rate is too high, the process of drawing and reducing the diameter of the welding wire becomes very difficult, and even the phenomenon of welding wire breaking occurs during the drawing process.
[0017] In the second aspect, the present application provides a method for preparing a corrosion-resistant and wear-resistant slag welding wire, comprising the following steps: crushing, drying, and mixing the raw materials used for the flux core to obtain the flux core, then filling the flux core into the rolled steel strip, closing the seams after filling, and drawing to obtain the corrosion-resistant and wear-resistant slag welding wire. During the filling process, the temperature of the flux core is controlled to 80-100°C.
[0018] Specifically, the raw materials used for the flux core are crushed to 80 mesh with a pass rate of 100%, then dried to remove moisture, and then loaded into a powder mixer for mixing to obtain the flux core, and then the coiled steel strip is placed on a steel strip winding machine, and then the steel strip is wound on an I-shaped barrel in sequence, and the ultrasonic water washing and drying box are turned on at the same time, and under this condition, a steel strip cleaning agent is added for surface cleaning, and then the rolled welding wire is wound on the welding wire winding disk in sequence, with each disk being wound 5-6 times, and the flux core is filled at a temperature of 80-100°C according to a certain filling rate. After the filling is completed, the welding wire is seamed and pulled until it passes through all molds, and the diameter of the welding wire reaches 2.35mm, thereby obtaining a corrosion-resistant and wear-resistant slag welding wire.
[0019] By adopting the above-mentioned technical scheme, the present application strictly controls the temperature during the process of filling the flux core, reduces the possibility of small particle seepage and large particle stratification during the filling feeding process, thereby improving the stability of the mixed split filling, so that the quality of the final welding wire and the welding part are relatively high.
[0020] Preferably, after crushing, the particle size of the drug core reaches 100% passing rate of 80 mesh and ≤20% passing rate of 200 mesh.
[0021] By adopting the above technical scheme, the flux core of the present application is mixed in a manner that all particles of a certain size pass through and a certain mass percentage of particles of another size pass through. At this time, the adhesion in the system is low, the fluidity is good, the smoke during welding is small, the splashing of coarse and fine particles is relatively slight, and the probability of wire breakage during the drawing process is extremely low, and the arc is also relatively stable, so that the quality of the final welding wire and the welding part is high.
[0022] In summary, this application has the following beneficial technical effects:
[0023] 1. The present application utilizes a variety of different flux core materials for compounding and strictly controls the addition amount of each component to obtain a welding wire that can significantly improve the hardness of the weld. Micro-carbon ferrochromium, ferroboron and ferrovanadium have a particularly significant synergistic effect, which can significantly reduce the number of cracks caused by the coarse rod-like structure of the crystal phase inside the weld, and promote the transformation of the coarse rod-like structure into a short rod-like structure, and improve the random distribution, presenting as much staggered random distribution as possible, thereby greatly improving the cross-tightness of the crystal phase structure inside the weld, and thus improving the wear resistance and corrosion resistance of the weld, thereby making the weld have a very high hardness, which can reach 45.5-46.1 HRC. The high-hardness weld can significantly increase the amount of steel passing through the weld structure. After testing, the arc section of the welding structure using the welding wire of the present application has a steel passing amount of not less than 800,000 tons, and the horizontal section has a steel passing amount of not less than 1.2 million tons, which can realize semi-automatic or fully automatic spiral welding and swing welding;
[0024] 2. The present application adds a certain amount of manganese nitride to the flux core, wherein the manganese element can provide a certain hardness for the weld, and the nitrogen element can be dissolved into the weld matrix at high temperature to form solid solution strengthening, and form nitrides with some elements in the system, playing a dual role, thereby significantly improving the wear resistance of the weld; at the same time, the nitrogen element can have a good synergistic effect with the tungsten powder to form a high-strength solid solution, causing lattice distortion in the system, thereby further improving the hardness of the weld;
[0025] 3. The present application strictly controls the temperature during the process of filling the core, reducing the possibility of small particle seepage and large particle stratification during the filling feeding process, thereby improving the stability of the mixed and separated filling, and gradually controlling the filling rate of the core, which not only ensures high density and low fluidity during filling, but also ensures smooth and unstuck subsequent drawing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a real shot of the welding part formed after welding using the corrosion-resistant and wear-resistant slag welding wire of the present application. DETAILED DESCRIPTION
[0027] Material Source
[0028] Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically:
[0029] Micro-carbon ferrochrome, with specific composition of Cr 65.42wt%, C 0.057wt%, S 0.012wt%, P 0.029wt%, Fe as the balance, 60 mesh;
[0030] Nickel powder, effective content 99.55wt%, 60 mesh;
[0031] High carbon ferromanganese, with specific composition of Mn 75.31wt%, C 6.69wt%, S 0.007wt%, Si 0.94wt%, P0.14wt%, balance Fe, 60 mesh;
[0032] Silicon manganese alloy, with the specific composition of Mn 65.34wt%, C 1.62wt%, S 0.025wt%, Si 17.23wt%, P0.15wt%, and the balance Fe, 60 mesh;
[0033] Rutile powder, the specific composition is C 0.008wt%, SiO 2 0.25wt%, TiO 2 95.54wt%, P 0.008wt%, crystal water 0.1wt%, S 0.008wt%, 80 mesh;
[0034] Quartz powder, the specific composition is C 0.021wt%, S 0.007wt%, Al 2 O 3 0.14wt%,SiO 2 98.23wt%, H 2 O0.1wt%, P 0.006wt%, Fe 2 O 3 0.025wt%, 80 mesh;
[0035] Fluorite powder, the specific composition is CaF 2 96.31wt%, C 0.15wt%, S 0.008wt%, SiO2 0.33wt%, P0.01wt%, 80 mesh;
[0036] Ferrovanadium, with a specific composition of V 50.13wt%, C 0.24wt%, S 0.031wt%, Si 0.97wt%, P 0.039wt%, and the balance Fe, 60 mesh;
[0037] Ferroniobium, with the specific composition of Nb 65.05wt%, C 0.25wt%, S 0.038wt%, Si 1.24wt%, P0.097wt%, Al 1.33wt%, and the balance is Fe, 60 mesh;
[0038] Fused magnesia, effective content 98.48wt%, 80 mesh;
[0039] Marble powder, effective content 98.52wt%, 80 mesh;
[0040] Ferrotitanium, specific composition: Ti 28.36wt%, C 0.077wt%, S 0.062wt%, Si 3.41wt%, P0.029wt%, Al 6.43wt%, 60 mesh;
[0041] Iron powder, with a specific composition of Fe 99.48wt%, the remainder of which are C, S, Si, P and Mn, 60 mesh;
[0042] Potassium feldspar, the specific composition is S 0.010wt%, Al 2 O 3 28.17wt%,SiO 2 63.29wt%, P 0.026wt%, K2O 11.23wt%, 80 mesh;
[0043] Sodium fluorosilicate, active ingredient 99.50wt%, drying loss at 105℃ 0.16wt%, free acid 0.08wt%, 80 mesh;
[0044] All the above materials were purchased from Nantong Jinyi Welding Materials Co., Ltd.
[0045] The present application is further described in detail below with reference to embodiments and comparative examples.
[0046] Example 1.1
[0047] A method for preparing a corrosion-resistant and wear-resistant slag welding wire comprises the following steps:
[0048] The raw materials used for the flux core (specific components are shown in Table 1) were crushed to 80 mesh with a pass rate of 100%, then dried at 400°C to remove moisture, and then loaded into a powder mixer for mixing to obtain a flux core. The coiled steel strip was then placed on a steel strip winding machine, and then the steel strip was wound on an I-shaped barrel in sequence. The ultrasonic water washing and drying box were turned on at the same time, and under this condition, a steel strip cleaning agent was added for surface cleaning. The rolled welding wire was then wound on the welding wire winding disk in sequence, with each disk being wound 6 times. The flux core was filled at a temperature of 80°C according to a filling rate of 42%. After the filling was completed, the welding wire was seamed and pulled at a speed of 3.5 m / s until it passed through all the dies. The diameter of the welding wire reached 2.35 mm, and a corrosion-resistant and wear-resistant slag welding wire was obtained.
[0049] Example 1.2
[0050] A method for preparing a corrosion-resistant and wear-resistant slag welding wire comprises the following steps:
[0051] The raw materials used for the flux core (specific components are shown in Table 1) were crushed to 80 mesh with a pass rate of 100%, then dried at 400°C to remove moisture, and then put into a powder mixer for mixing to obtain a flux core. The coiled steel strip was then placed on a steel strip winding machine, and then the steel strip was wound on an I-shaped barrel in sequence. The ultrasonic water washing and drying box were turned on at the same time, and under this condition, a steel strip cleaning agent was added for surface cleaning. The rolled welding wire was then wound on the welding wire winding disk in sequence, with each disk being wound 6 times. At a temperature of 100°C, the flux core was filled at a filling rate of 35%. After the filling was completed, the welding wire was jointed and pulled at a speed of 3.5 m / s until it passed through all the dies. The diameter of the welding wire reached 2.35 mm, and a corrosion-resistant and wear-resistant slag welding wire was obtained.
[0052] Example 1.3
[0053] A method for preparing a corrosion-resistant and wear-resistant slag welding wire comprises the following steps:
[0054] The raw materials used for the flux core (specific components are shown in Table 1) were crushed to 80 mesh with a pass rate of 100%, then dried at 400°C to remove moisture, and then loaded into a powder mixer for mixing to obtain a flux core. The coiled steel strip was then placed on a steel strip winding machine, and then the steel strip was wound on an I-shaped barrel in sequence. The ultrasonic water washing and drying box were turned on at the same time, and under this condition, a steel strip cleaning agent was added for surface cleaning. The rolled welding wire was then wound on the welding wire winding disk in sequence, with each disk being wound 6 times. The flux core was filled at a temperature of 90°C according to a filling rate of 37.5%. After the filling was completed, the welding wire was seamed and pulled at a speed of 3.5 m / s until it passed through all the dies. The diameter of the welding wire reached 2.35 mm, and a corrosion-resistant and wear-resistant slag welding wire was obtained.
[0055] Table 1 Specific components of the core of Examples 1.1-1.3 / kg
[0056]
[0057] Example 2.1
[0058] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that 4 kg of manganese nitride is also added, the amount of iron is 5 kg, and the rest is the same as Example 1.1.
[0059] Example 2.2
[0060] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that 4.5 kg of manganese nitride is also added, the amount of iron is 4.5 kg, and the rest is the same as Example 1.1.
[0061] Example 2.3
[0062] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that 5 kg of manganese nitride is also added, the amount of iron is 4 kg, and the rest is the same as Example 1.1.
[0063] Example 2.4
[0064] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 2.1 in that: the amount of manganese nitride used is 4.6 kg, the amount of tungsten powder used is 2 kg, the amount of iron used is 4.4 kg, and the rest is the same as Example 2.1.
[0065] Example 2.5
[0066] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 2.1 in that: the amount of manganese nitride used is 4.6 kg, the amount of tungsten powder used is 2.2 kg, the amount of iron used is 4.2 kg, and the rest is the same as Example 2.1.
[0067] Example 2.6
[0068] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 2.1 in that: the amount of manganese nitride used is 4.6 kg, the amount of tungsten powder used is 2.5 kg, the amount of iron used is 3.9 kg, and the rest is the same as Example 2.1.
[0069] Example 3.1
[0070] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the flux is 3kg of potassium feldspar and 2kg of zinc oxide, and the rest is the same as Example 1.1.
[0071] Example 3.2
[0072] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the flux is 4 kg of sodium fluorosilicate and 1 kg of albite, and the rest is the same as Example 1.1.
[0073] Example 3.3
[0074] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the flux is 1 kg of sodium fluorosilicate, 1.5 kg of zinc oxide and 2.5 kg of potassium feldspar, and the rest is the same as Example 1.1.
[0075] Example 3.4
[0076] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the flux is 3kg of sodium feldspar, 1.5kg of sodium fluorosilicate and 0.5kg of potassium feldspar, and the rest is the same as Example 1.1.
[0077] Example 3.5
[0078] A method for preparing a corrosion-resistant and wear-resistant slag welding wire, which is different from Example 1.1 in that the flux is 1.25kg sodium fluorosilicate, 1.25kg potassium feldspar, 1.25kg sodium feldspar and 1.25kg zinc oxide, and the rest is the same as Example 1.1.
[0079] Example 3.6
[0080] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the flux is 3.75 kg of sodium fluorosilicate and 1.25 kg of potassium feldspar, and the rest is the same as Example 1.1.
[0081] Example 3.7
[0082] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the flux is 2.5 kg of sodium fluorosilicate and 2.5 kg of potassium feldspar, and the rest is the same as Example 1.1.
[0083] Example 3.8
[0084] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the flux is 1.25 kg of sodium fluorosilicate and 3.75 kg of potassium feldspar, and the rest is the same as Example 1.1.
[0085] Example 4.1
[0086] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from that of Example 1.1 in that the filling rate of the flux core is 40%, and the rest is the same as that of Example 1.1.
[0087] Example 4.2
[0088] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the filling rate of the flux core is 39%, and the rest is the same as Example 1.1.
[0089] Example 4.3
[0090] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from that of Example 1.1 in that the filling rate of the flux core is 38%, and the rest is the same as that of Example 1.1.
[0091] Example 4.4
[0092] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from Example 1.1 in that the filling rate of the flux core is 37%, and the rest is the same as Example 1.1.
[0093] Example 4.5
[0094] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from that of Example 1.1 in that the filling rate of the flux core is 35%, and the rest is the same as that of Example 1.1.
[0095] Example 4.6
[0096] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from that of Example 1.1 in that the filling rate of the flux core is 50%, and the rest is the same as that of Example 1.1.
[0097] Example 4.7
[0098] A method for preparing a corrosion-resistant and wear-resistant slag welding wire is different from that of Example 1.1 in that the filling rate of the flux core is 30%, and the rest is the same as that of Example 1.1.
[0099] Example 5
[0100] A method for preparing a corrosion-resistant and wear-resistant slag welding wire, which is different from Example 1.1 in that: after crushing, the particle size of the flux core reaches 80 mesh pass rate 100%, and the 200 mesh pass rate ≤20%, and the rest is the same as Example 1.1.
[0101] Comparative Example 1
[0102] The difference from Example 1.1 is that all ferroboron is replaced by iron, and the rest is the same as Example 1.1.
[0103] Comparative Example 2
[0104] The difference from Example 1.1 is that all vanadium and iron are replaced by iron, and the rest is the same as Example 1.1.
[0105] Comparative Example 3
[0106] The difference from Example 1.1 is that during the filling process, the temperature of the medicine core is controlled at 70° C., and the rest is the same as Example 1.1.
[0107] Comparative Example 4
[0108] The difference from Example 1.1 is that during the filling process, the temperature of the medicine core is controlled at 120° C., and the rest is the same as Example 1.1.
[0109] Performance Testing
[0110] 1. Wear resistance test: The hardness of the welded parts of the welding wires of the embodiment and the comparative example was measured by using a HS121 hardness tester;
[0111] 2. Corrosion resistance test: The corrosion rate of the welded parts obtained by welding the welding wires of the embodiment and the comparative example was measured according to the standard of JB / T 7901. The corrosion source was cooling water containing 5wt% sulfuric acid and 5wt% hydrofluoric acid, and the whole was immersed for 24h.
[0112] 3. Anti-pore capability: The surface of the welded part obtained by welding the welding wire of the embodiment is smooth and free of pores. Figure 1 As shown;
[0113] 4. Steel overload test: The steel overload of the welding part obtained after welding with the welding wire of the embodiment and the comparative example is recorded according to the actual use situation, which is divided into the steel overload of the curved section and the steel overload of the straight section. The steel overload is the average value, and the recording period is one year.
[0114] Table 2 Performance test table
[0115]
[0116] Data Analysis:
[0117] As can be seen from Table 2, the hardness of the welded part obtained by welding the welding wire obtained in Examples 1.1-1.3 of the present application is 45.5-46.1 HRC, and the corrosion rate of the welding wire after being fully immersed in cooling water containing 5wt% sulfuric acid and 5wt% hydrofluoric acid for 24 hours is 1.44-1.46 mg / cm 2 ·h, and if Figure 1 As shown, the surface of the welded part obtained after welding is smooth and free of pores, the amount of steel passed in the curved section is not less than 800,000 tons, and the amount of steel passed in the straight section is not less than 1.2 million tons, proving that the present application obtains a welding wire that can significantly improve the hardness of the weld by compounding a variety of different flux core materials and strictly controlling the amount of each component added, among which micro-carbon ferrochromium, ferroboron and ferrovanadium play a particularly significant synergistic effect, which can greatly reduce the number of cracks caused by the coarse rod-like structure of the crystal phase inside the weld, and promote the transformation of the coarse rod-like structure to a short rod-like structure, and improve the randomness of the distribution, presenting as much staggered random distribution as possible, thereby greatly improving the cross-tightness of the crystal phase structure inside the weld, and also improving the wear resistance and corrosion resistance of the weld, thereby making the weld have a very high hardness, and the high-hardness weld can greatly increase the amount of steel passed in the welding structure;
[0118] The hardness, corrosion rate, steel overload in the curved section and steel overload in the straight section of Examples 2.1-2.3 are significantly better than those of Example 1.1, which proves that the present application adds a certain amount of manganese nitride to the flux core to provide a certain hardness to the weld using manganese, and the nitrogen element can be dissolved into the weld matrix at high temperature to form solid solution strengthening, and form nitrides with some elements in the system, playing a dual role, thereby significantly improving the wear resistance of the weld; at the same time, the nitrogen element can have a good synergistic effect with the tungsten powder to form a high-strength solid solution, causing lattice distortion in the system, thereby further improving the hardness of the weld;
[0119] In Examples 2.4-2.6, the present application further controls the amount of manganese nitride added, and adjusts the amount of tungsten powder added according to the amount of manganese nitride added. The hardness of the welded part of Example 2.5 reaches 50.8HRC, and the corrosion rate is as low as 1.24mg / cm 2 h, the amount of steel passed through the curved section is not less than 900,000 tons, and the amount of steel passed through the straight section is not less than 1.35 million tons. All data are better than those of Example 2.4 and Example 2.6, proving that the present application strictly controls the amount of manganese nitride and tungsten powder added, thereby strictly controlling the weight ratio of the two, and further optimizing the wear resistance and hardness of the weld;
[0120] In Examples 3.1-3.8, the present application adjusted the components of the flux and the amounts of each component, wherein the welding wire obtained in Examples 3.6-3.8 had a hardness of 48.4-48.9 HRC at the welded portion after welding, and a corrosion rate of 1.30-1.32 mg / cm2 when fully immersed in cooling water containing 5 wt% sulfuric acid and 5 wt% hydrofluoric acid for 24 h. 2 h, proving that the present invention effectively promotes the melting of non-metallic elements in the system of the present invention by utilizing sodium fluorosilicate and potassium feldspar in a weight ratio of (1-3): (1-3), thereby improving the hardness of the weld and the smoothness of the weld surface;
[0121] After welding, the welded parts of the welding wires obtained in Examples 4.1-4.3 were immersed in cooling water containing 5wt% sulfuric acid and 5wt% hydrofluoric acid for 24 hours, and the corrosion rate was 1.23-1.26 mg / cm 2h, which is much lower than that of Example 1.1. Meanwhile, the corrosion rates of Examples 4.1-4.5 and Example 1.1 are lower than those of Examples 4.6-4.7, which proves that the present application controls the filling rate of the flux core step by step, which not only ensures the high compactness and low fluidity during filling, but also ensures smooth and unstuck process during the subsequent drawing process. If the filling rate is too low, the components of the flux core are prone to flow during drawing and welding, resulting in unstable arc or even arc breaking during welding. At the same time, the inside of the welding wire is loose, and gas will be brought into the molten pool during welding, increasing the number of pores in the weld and greatly reducing the corrosion resistance. If the filling rate is too high, the process of drawing and reducing the diameter of the welding wire becomes very difficult, and even the phenomenon of welding wire breaking occurs during the drawing process.
[0122] The data of Example 5 are all better than those of Example 1.1, which proves that the present application adopts a mixing method in which all particles of a certain particle size pass through and a certain mass percentage of the flux core of another particle size pass through, which greatly reduces the cohesion in the system, improves fluidity, reduces the smoke generated during welding, and alleviates the splashing of coarse and fine particles. In addition, the probability of wire breakage during the drawing process is low, and the arc is stable, so that the quality of the final welding wire and the welding part is high;
[0123] The data of comparative examples 1-2 are inferior to those of example 1.1, which proves that the present application obtains a welding wire capable of significantly improving the hardness of the weld by compounding a variety of different flux core materials and strictly controlling the addition amount of each component, wherein micro-carbon ferrochromium, ferroboron and ferrovanadium play a particularly significant synergistic effect, which can significantly reduce the number of cracks caused by the coarse rod-like structure of the crystal phase inside the weld, and promote the transformation of the coarse rod-like structure into a short rod-like structure, and improve the randomness of the distribution, presenting as much staggered random distribution as possible, thereby significantly improving the cross-tightness of the crystal phase structure inside the weld, and also improving the wear resistance and corrosion resistance of the weld, thereby making the weld have a very high hardness, and the high-hardness weld can significantly increase the amount of steel passing through the welding structure;
[0124] The data of comparative examples 3-4 are all inferior to those of example 1.1, which proves that the present application reduces the possibility of small particle seepage and large particle stratification during the filling feeding process by strictly controlling the core temperature, thereby improving the stability of the mixed split filling, so that the quality of the final welding wire and the welding part are higher.
[0125] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A corrosion-resistant and wear-resistant slag welding wire, the raw materials used include flux core and steel strip, characterized in that: The raw materials used in the drug core include the following components in percentage by mass: Micro-carbon ferrochrome 35-38%; Nickel powder 8-10%; Ferroboron 3-5%; High carbon ferromanganese 2-4%; Silicon manganese alloy 2-4%; Aluminum powder 1-5%; Rutile powder 4-8%; Quartz powder 1-3%; Fluorite powder 4-6%; Ferrovanadium 0.5-2%; Ferroniobium 1-2%; Cobalt powder 0.5-1%; Tungsten powder 2-2.5%; Potassium carbonate powder 1-2%; Fused magnesia 2-5%; Marble powder 1-5%; Ferrotitanium 1-2%; Flux 3-5%; The balance is iron.
2. The corrosion-resistant and wear-resistant slag welding wire according to claim 1, characterized in that: The raw materials used for the drug core also include manganese nitride added in an amount of 4-5wt%.
3. The corrosion-resistant and wear-resistant slag welding wire according to claim 2, characterized in that: The added amount of the manganese nitride is 4.6wt%, and the added amount of the tungsten powder is 2.2wt%.
4. The corrosion-resistant and wear-resistant slag welding wire according to claim 1, characterized in that: The flux includes one or more of sodium fluorosilicate, potassium feldspar, sodium feldspar and zinc oxide.
5. The corrosion-resistant and wear-resistant slag welding wire according to claim 4, characterized in that: The flux comprises sodium fluorosilicate and potassium feldspar in a weight ratio of (1-3):(1-3).
6. The corrosion-resistant and wear-resistant slag welding wire according to claim 1, characterized in that: The filling rate of the medicine core is 35-42%.
7. The corrosion-resistant and wear-resistant slag welding wire according to claim 6, characterized in that: The filling rate of the medicine core is 38-40%.
8. A method for preparing the corrosion-resistant and wear-resistant slag welding wire according to any one of claims 1 to 7, comprising the following steps: The raw materials used for the flux core are crushed, dried, and mixed to obtain the flux core, and then the flux core is filled into the rolled steel strip. After the filling is completed, the seams are closed and drawn to obtain a corrosion-resistant and wear-resistant slag welding wire, characterized in that during the filling process, the temperature of the flux core is controlled to 80-100°C.
9. The method for preparing the corrosion-resistant and wear-resistant slag welding wire according to claim 8, characterized in that: After crushing, the particle size of the drug core reaches 100% passing rate of 80 mesh and ≤20% passing rate of 200 mesh.
Citation Information
Patent Citations
High-weather-resistance fireproof steel welding alkaline flux-cored wire
CN110293332A
Flux-cored wire and preparation method thereof
CN118023760A